Ziryab Albutani Almusoli And His Impact On The Progress Of Musicology And The Arts Singing، Cooking And Fashion - Almnshdawy, Khdaer A. (Humanities Journal of University of Zakho, 2013)
Ziryab Albutani Almusoli represents a prominent enlightenment in the history of Islamic civilization in special and the history of human thought in general, because of his effective contribution in transferring the eastern musical heritage to Andalusia and then to Europe.In this research, we tried to find out new things that relate to the life and the heritage of Ziryab Albutani Almusoli, including: according to historical evidences, it’s approved that Ziryab’s nationality is Kurdish and he belongs to (Jazeerat Butan); the city of Kurdish origin, he also is not black as it’s mentioned in some references, describing ziryab as black is not based on acceptable historical evidences. Besides, Ziryab was not only interested in singing and music, in addition to his creativity in this artistic direction, he was one of the encyclopedic scientists who brought more than one science and art together, including the sciences of history, geography and astronomy, as well as the arts of literature and poetry .... Further, he was creative in aesthetics and fashion design; he found new hairstyles and many ways in taking care of the beauty of the skin. More ever, he designed a lot of costumes that were suitable for each season of the year.Thus, Ziryab was one of the earlier of those who dealt with musicology, singing, culinary arts, organizing banquets, fashion design, elegance according to applicable and precise technical basis and the proof is that a lot of the foundations laid by Ziryab is still used until now.